2016
DOI: 10.1007/s10854-016-5933-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of the recently synthesized (Zr3−x Ti x )AlC2 MAX phases

Abstract: In the present study we investigate the structural, Fermi surface and optical properties of the recently synthesized (Zr 3-x Ti x )AlC 2 MAX phases using density functional theory. The inclusion of Ti in the M site causes a reduction of both the a and c lattice parameters. The reduction of the a lattice parameter with respect to Ti content is more significant and this is reflected in the increase of the c/a ratio. The Fermi surfaces are formed mainly due to the low-dispersive transition metal d-like orbitals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…On the other hand, (Zr 1-x ,Ti x ) 3 AlC 2 MAX phases were recently claimed to have been successfully synthesized, but the results of that study have not yet been published. 13 Solid solutions reported to contain Ti, Zr, Al and C include: (Ti,M) 2 AlC with M = V, Nb, Ta, Cr, [14][15][16][17] (Nb,Zr) 2 AlC, 15,18 (Ti,V) 3 AlC 2 , 18 (Ti,Nb) 4 AlC 3 , 19 and (Nb,Zr) 4 AlC 3 . 20,21 In this study, Ti was added to the Zr-Al-C system in an attempt to synthesize (Zr 1-x ,Ti x ) 3 AlC 2 (ZT312) and (Zr 1-x ,Ti x ) 2 AlC (ZT211) MAX phase solid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, (Zr 1-x ,Ti x ) 3 AlC 2 MAX phases were recently claimed to have been successfully synthesized, but the results of that study have not yet been published. 13 Solid solutions reported to contain Ti, Zr, Al and C include: (Ti,M) 2 AlC with M = V, Nb, Ta, Cr, [14][15][16][17] (Nb,Zr) 2 AlC, 15,18 (Ti,V) 3 AlC 2 , 18 (Ti,Nb) 4 AlC 3 , 19 and (Nb,Zr) 4 AlC 3 . 20,21 In this study, Ti was added to the Zr-Al-C system in an attempt to synthesize (Zr 1-x ,Ti x ) 3 AlC 2 (ZT312) and (Zr 1-x ,Ti x ) 2 AlC (ZT211) MAX phase solid solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of a magnetic MAX phase has extended the list of interesting properties of MAX family [7]. To date, a large number of MAX phase compounds have been synthesized [8][9][10][11][12][13][14][15][16][17] and their physical properties have also been studied [18][19][20][21][22][23][24][25][26][27]. Very recently, Lapauw et al has synthesized Hf 3 AlC 2 [28], which is the first member of 312 MAX phases in the Hf-Al-C system.…”
Section: Introductionmentioning
confidence: 99%
“…The strain can affect the imaginary part of the dielectric function and further affect the optical properties of semiconductor materials. [42][43][44][45][46] For example, Cakir et al [8] thought that strain has a significant effect on the optical properties and can tune the optical band gap of monolayer black phosphorus from 0.38 eV to 2.07 eV. Yang et al [30] found that strain greatly changed the optical properties of ReSe 2 .…”
mentioning
confidence: 99%